2023
DOI: 10.1089/chi.2022.0171
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Gut Microbiome: A Cluster-Randomized, Controlled, Pilot Feasibility Study

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…Here, we calculated BMI using the Child & Teen BMI Calculator (BMI Calculator Child and Teen | Healthy Weight | CDC). Lower BMI was associated with a decrease in fecal Tenericutes and an increase in Actinobacteria (Frenn et al, 2023). In our study, we found significant differences in gut microbiota bacterial composition and function along with BMI.…”
Section: Discussionsupporting
confidence: 58%
“…Here, we calculated BMI using the Child & Teen BMI Calculator (BMI Calculator Child and Teen | Healthy Weight | CDC). Lower BMI was associated with a decrease in fecal Tenericutes and an increase in Actinobacteria (Frenn et al, 2023). In our study, we found significant differences in gut microbiota bacterial composition and function along with BMI.…”
Section: Discussionsupporting
confidence: 58%